2007
DOI: 10.1038/sj.leu.2404578
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiological diversity in infant acute lymphoblastic leukemia is related to the occurrence and type of MLL gene rearrangement

Abstract: The aim of this study was to identify immunobiological subgroups in 133 infant acute lymphoblastic leukemia (ALL) cases as assessed by their immunophenotype, immunoglobulin (Ig) and T-cell receptor (TCR) gene rearrangement pattern, and the presence of mixed lineage leukemia (MLL) rearrangements. About 70% of cases showed the pro-B-ALL immunophenotype, whereas the remaining cases were common ALL and pre-B-ALL. MLL translocations were found in 79% of infants, involving MLL-AF4 (41%), MLL-ENL (18%), MLL-AF9 (11%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
71
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 52 publications
6
71
1
1
Order By: Relevance
“…In Case 6, a Vh replacement in a complete Vh-Dh-Jh complex was detected, corresponding to a secondary rearrangement. The absence of Ig or TCR in Case 8 and the detection of only an IGH rearrangement in Case 9, both MLL positive leukemias, could be related to the association of MLL with a more immature pattern [28].…”
Section: Discussionmentioning
confidence: 91%
“…In Case 6, a Vh replacement in a complete Vh-Dh-Jh complex was detected, corresponding to a secondary rearrangement. The absence of Ig or TCR in Case 8 and the detection of only an IGH rearrangement in Case 9, both MLL positive leukemias, could be related to the association of MLL with a more immature pattern [28].…”
Section: Discussionmentioning
confidence: 91%
“…Thus far, at least 64 different MLL partner genes have been identified in acute leukemia patients [33,34]. Despite this exceptionally high number of different partner genes, only six different partner genes are found in w85% of acute leukemias with an MLL fusion gene: AF4, AF9, ENL, AF10, AF6 and ELL [34].…”
Section: Future Immunobead Assay: Multiplex Mll Tubementioning
confidence: 99%
“…This multiplex immunobead assay can detect in a single step the most frequently occurring MLL fusion proteins in MLL þ acute leukemias. (Table 3) [33,34]. Also, the prognosis of these MLL gene aberrations ranges from mainly poor for most MLL gene aberrations to fairly good for, for instance, MLL-AF9 in AML.…”
Section: Future Immunobead Assay: Multiplex Mll Tubementioning
confidence: 99%
“…Two studies reported in this issue of Leukemia demonstrate a high prevalence of immature, nonproductive and/or oligoclonal antigen-receptor gene rearrangements in infant ALL with MLL fusions. 8,10 Overall, infant leukemias had gene rearrangement patterns that were different from those of leukemias diagnosed in older children (including those with MLL fusions), 8,10 suggesting that infant cases originated mostly from a lymphoid progenitor with germline or incompletely rearranged antigen-receptor genes. 8,10 Leukemogenic events during fetal development may also result in distinct MLL breakpoints.…”
mentioning
confidence: 99%
“…8,10 Overall, infant leukemias had gene rearrangement patterns that were different from those of leukemias diagnosed in older children (including those with MLL fusions), 8,10 suggesting that infant cases originated mostly from a lymphoid progenitor with germline or incompletely rearranged antigen-receptor genes. 8,10 Leukemogenic events during fetal development may also result in distinct MLL breakpoints. Thus, Reichel et al 11 found that 13 of 24 infants less than 1 year of age had breakpoints in the telomeric part of the MLL breakpoint cluster region, whereas 29 of 34 children and adults had breakpoints in the centromeric part of the MLL breakpoint cluster region.…”
mentioning
confidence: 99%